Topical Probiotics: More Than a Skin Deep - Mohammed Habeebuddin; Ranjith Kumar Karnati; Predeepkumar Narayanappa Shiroorkar; Sreeharsha Nagaraja; Syed Mohammed Basheeruddin Asdaq; Md. Khalid Anwer; Santosh Fattepur (MDPI AG, 2022)
Skin, an exterior interface of the human body is home to commensal microbiota and also acts a physical barrier that protects from invasion of foreign pathogenic microorganisms. In recent years, interest has significantly expanded beyond the gut microbiome to include the skin microbiome and its influence in managing several skin disorders. Probiotics play a major role in maintaining human health and disease prevention. Topical probiotics have demonstrated beneficial effects for the treatment of certain inflammatory skin diseases such as acne, rosacea, psoriasis etc., and also found to have a promising role in wound healing. In this review, we discuss recent insights into applications of topical probiotics and their influence on health and diseases of the skin. Patents, commercially available topical probiotics, and novel probiotic impregnated fabrics have been emphasized. A thorough understanding of the relationship between probiotics and the skin microbiome is important for designing novel therapeutic approaches in using topical probiotics.